Draft Annual Plan [1986-87] & Part-II - Plan Proposals in Detail - Planning Commission (Planning Commission, 1985)
A large number of crop pest (insects and disease) are one of the major constraints for increasing yields and therefore plant protection programmes like subsidizing pesticides and plant protection equipment, conducting demonstrations etc. will be implemented to increase yield of the crops.
Directorate of Planning Statistics and Evaluation
Directorate of Planning Statistics and Evaluation